Human to Human Transmission of Brucella Melitensis - Patrice Vigeant; Jack Mendelson; Mark A Miller (Canadian Journal of Infectious Diseases)
Human brucellosis is acquired mainly through contact with infected animal tissues, ingestion of unpasteurized dairy products or infected aerosols. Person to person transmission is still considered uncertain. The case of a woman diagnosed with proven brucellosis after her husband suffered a relapse of bacteremia with Brucella melitensis biotype 3, which was originally acquired abroad by eating goat cheese, is described. It was postulated that person to person spread of brucellosis is a likely mode of transmission in this case.